Iowa RBA, October 5, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for October 5, 1998. Highlights include Sabine's Gull, Prairie Falcon, Yellow Rail, Little Blue Heron, and Snowy Egret. Includes notes for updates for October 6, October 7, and October 9. Epson - sheet feed/flatbed